The effects of mobile CRM activities on trust-based commitment. (1st January 2011) - Sohn, Changsoo; Lee, Dong-Il; Lee, Hyejun
This study analysed the effects of mobile CRM activities on trust-based commitment by evaluating mobile CRM activities from customer's standpoint using three variables; contents differentiation, contact frequency, and contents repetition. The perceived evaluation of mobile CRM activities explains trust, which plays a role of creating stronger customer commitment. Commitment consists of three constructs; affective commitment, continuance commitment, and normative commitment. Questionnaire surveys were conducted to verify the research model. The data were used to test hypotheses by using structural equation modelling (SEM). The results showed that CRM activities (content differentiation and contact frequency) contribute to build trust-based commitment (affective commitment, continuance commitment, and normative commitment). The results from this research may serve as a guideline for companies aiming to more effectively build trust-based commitment through mobile CRM activities.